The analysis of proverb meaning in Tenggelamnya kapal van der wijck film:a metaphorical approaches - Kiki Karlina; Dodi Oktariza; Vera Magria (Universitas Muara Bungo, 2017)
This thesis analyzes about proverbs meaning found in Tenggelamnya Kapal Van der Wijck film.There are some aims of the research, namely (1) to describe the proverbs meaning that belong to traditionaland cognitive metaphor (2) to describe the functions of proverbs meaning and (3) to explain the religion andculture values of proverbs used in Tenggelamnya Kapal Van der Wijck film. This research was conducted byusing descriptive qualitative method through applying several stages. The first one was by collecting datathrough three ways: (1) document technique, (2) observation technique and (3) note technique. The secondone analyzing data use identity method (metode padan). The third, the writer uses metaphor approaches toget the meaning of proverb that found in Tenggelamnya Kapal Van der Wijck film. The using of metaphor inthis research has two approaches those are traditional and cognitive metaphor. Meanwhile, the functionsand the values that contained in proverbs are explained in this research as well. From the result of theresearch, this research shows that proverb as the heritage of the culture and gives contribution significantlyto development of language as part of Minangkabau culture community.Key word: Proverbs, Minangkabau, Metaphorical Analysis